Peningkatan Kemampuan Kepekaan Bilangan Anak Usia 4–5 Tahun Melalui Media Pohon Angka di TK Theobroma 2 Gondang (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to determine the effectiveness of the number tree media in improving number sense skills among 4-5-year-old children at TK Theobroma 2 Gondang. The research employed a Classroom Action Research (CAR) method using the Kemmis & McTaggart model, conducted over two cycles. Each cycle involved planning, action, observation, and reflection. Data were collected through observation sheets based on three main indicators: recognizing number symbols (1-10), using number symbols to count, and matching quantities with number symbols. The results showed an increase in the average score from 2.53 in cycle I to 3.14 in cycle II. The number of children in the “Good” and “Very Good” categories increased from 6 children (50%) to 11 children (91.66%). According to Arikunto’s success criteria, this research is considered successful. The use of the number tree media proved effective in helping children understand numerical concepts in a visual and manipulative manner, while also promoting active learning. These findings highlight the importance of contextual and exploratory learning media in supporting early childhood cognitive development, especially in basic mathematics education.